Heat wave effects on the behavior and life-history traits of sedentary antlions. (22nd September 2020) - Miler, Krzysztof; Stec, Daniel; Czarnoleski, Marcin
Abstract: Research on the behavioral responses of animals to extreme weather events, such as heat wave, is lacking even though their frequency and intensity in nature are increasing. Here, we investigated the behavioral response to a simulated heat wave in two species of antlions (Neuroptera: Myrmeleontidae). These insects spend the majority of their lives as larvae and live in sandy areas suitable for a trap-building hunting strategy. We used larvae of Myrmeleon bore and Euroleon nostras, which are characterized by different microhabitat preferences—sunlit in the case of M. bore and shaded in the case of E. nostras . Larvae were exposed to fluctuating temperatures (40 °C for 10 h daily and 25 °C for the remaining time) or a constant temperature (25 °C) for an entire week. We found increased mortality of larvae under heat. We detected a reduction in the hunting activity of larvae under heat, which corresponded to changes in the body mass of individuals. Furthermore, we found long-term consequences of the simulated heat wave, as it prolonged the time larvae needed to molt. These effects were pronounced in the case of E. nostras but did not occur or were less pronounced in the case of M. bore, suggesting that microhabitat-specific selective pressures dictate how well antlions handle heat waves. We, thus, present results demonstrating the connection between behavior and the subsequent changes to fitness-relevant traits in the context of a simulated heat wave. These results illustrate how even closely related species may react differently to the same event. Abstract : Animals must cope with what the environment throws at them. When that is a heat wave, sedentary insect predators, such as antlions, either reduce hunting activity and suffer fitness-relevant consequences or remain actively hunting and successfully buffer against harsh conditions. The type of displayed reaction depends on the ecological and evolutionary characteristics of a species experiencing a heat wave.